Pharmaceutical and non-pharmaceutical antihypertensive therapy in Type 2 diabetes mellitus patients - S. G. Malishevsky (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To study ahtihypertensive therapy effects on carbohydrate metabolism in patients with arterial hypertension (AH) and Type 2 diabetes mellitus (DM-2). Material and methods. In total, 84 AH and DM-2 patients were examined: males and females aged 45-78 years (mean age 62.56±15.44 years). General physical examination, anthropometry, body mass index (BMI) calculation, blood pressure (BP), heart rate measurement, electrocardiography, general blood and urine assays, glucose tolerance test were performed; lipid profile, glycemia, fasting insulin, creatinine levels were measured. Results. In all participants, systolic and diastolic BP (SBP, DBP) levels decreased (p=0.001; p=0.001, respectively). Six months later, in Group I (BMI<30) mean SBP decreased from 160.9 to 145 mm Hg; mean DBP – from 94.8 to 86.8 mm Hg. In Group II (BMI 30-35) these figures were 160.8 to 144.5 mm Hg, and 97.3 to 88 mm Hg, respectively. In Group III (BMI>35), they were 167.9 to 148.9 mm Hg, and 99.8 to 87.6 mm Hg, respectively. In all three groups, glucose and cholesterol dynamics was not significant. Conclusion. In DM-2 patients receiving hypoglycemic agents, antihypertensive therapy did not affect carbohydrate metabolism. Significant cholesterol level decrease was observed in patients on strict fat-free and low-carbohydrate diet.